Brush Cytology with Immunocytochemical Evaluation of VEGF Expression versus Biopsy in Clinically Precancerous Laryngeal Lesions: Can We Diagnose Laryngeal Cancer Only with Brush Cytology? - Angelos Chatziavramidis; Zinovia Tsinaslanidou; Rozalia Valeri; Iordanis Konstantinidis; Jannis Constantinidis (Analytical Cellular Pathology)
Introduction. Laryngeal squamous cell carcinoma (LSCC) is the most common SCC of the head and neck. The high incidence of this malignancy and the low survival rate necessitate the development of novel diagnostic approaches. Aim of this study is to compare the diagnostic value of laryngeal brush cytology combined with VEGF immunocytochemistry versus histopathology of clinically precancerous lesions of the larynx. Material and Methods. Thirty patients with precancerous or suspected malignant laryngeal lesions underwent microlaryngoscopy, during which samples were taken for cytological, immunocytochemical, and histological analysis. Cytology and histology results were classified as follows: benign lesions, atypia/moderate dysplasia, and malignancy, whereas the expression of VEGF was evaluated as strong, moderate, weak, and zero expression, based on the percentage of cells stained. Results. The cytology results were in accordance with the histology results in 86.7% of the patients. The exfoliative cytology’s sensitivity was estimated at 85% and its specificity at 90%. Its positive prognostic value was 94%, while its negative prognostic value was 75%. The additional immunocytochemical evaluation of VEGF expression increased all the noted parameters. Discussion. Exfoliative cytology of laryngeal lesions is a minimal-invasive, easily applicable procedure during microlaryngoscopy and reliable in terms of diagnostic value. Under certain conditions it could be held also in local anesthesia. Concurrent immunocytochemical analysis of VEGF expression further enhances its diagnostic value.